DAMPAK PENAMBANGAN MARMER DI DESA BESOLE KECAMATAN BESUKI KABUPATEN TULUNGAGUNG TERHADAP LINGKUNGAN - Vavo, Prinanda; Vinansia, Aretsa; Rahayu, Putri; Rosa, Yayang Yulia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The marble-producing village of Besole encourages its residents to do business other than farming, namely processing marble into various manufactured products. It was the desire to live in prosperity that ultimately caused some of the people of Besole Village to switch their livelihoods from farmers to people who work in home industries. The research method used is a qualitative method using library research. Literature research is an activity that examines various types of relevant sources. The purpose of this study is to determine: the impact that occurs due to marble mining on the environment. Apart from that marble mining also produces waste which causes environmental pollution, but the people of Besole village can use this waste to become something useful